The Energy Transition and the Value of Capacity Remuneration Mechanisms - Cinzia Bonaldo; Fulvio Fontini; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2022)
Capacity Remuneration Mechanisms (CRM) can be used in power markets to overtake market failures, reaching security of supply. However, investment in capacity is a dynamic process, that depends on the evolution of prices and costs overtime. In our paper we study the capacity remuneration value through a CRM depending on three possible different technologies that participate to the market: a Variable Renewable Energy (VRE) source; a thermal efficient plant (i.e. Combine Cycle Gas Turbine) and a brown plant (i.e. coal). We shall see that these three types of capacities can be framed by means of a common theoretical framework, whose level of complexity increases as the uncertainty rises, moving from the simplest scheme (VRE technology) to the most complex one (coal power plant). For these different technological provisions, we consider how to evaluate them focusing on their investment value by adopting a stochastic approach; we first provide a theoretical framework and then sensitivity analysis and calibration results. We show that for all three technology considered the effect of the CRM is to cap the firm revenues and as consequence it decreases their value.
Keywords: Q40; C60; D80; 330; energy transition; capacity remuneration mechanism; price cap; renewable energies; investment value